Resting-State Stereotactic Electroencephalography May Help Localize Epileptogenic Brain Regions. (1st September 2019) - Goodale, Sarah; Gonzalez, Hernan F J; Johnson, Graham Walter; Gupta, Kanupriya; Rodriguez, William; Shults, Robert; Rolston, John D; Dawant, Benoit M; Morgan, Victoria; Englot, Dario J
Abstract: INTRODUCTION: Stereotactic electroencephalography (SEEG) is a minimally invasive neurosurgical method to localize epileptogenic brain regions in epilepsy, but requires days in the hospital with interventions to trigger several uncomfortable seizures. Our goal is to make initial progress in the development of network analysis methods to identify epileptogenic brain regions using brief, resting-state SEEG data segments, without requiring seizure recordings. METHODS: In a cohort of 15 adult focal epilepsy patients undergoing SEEG, we evaluated functional connectivity (alpha-band imaginary coherence) across sampled regions using brief (2 min) resting-state data segments. Bootstrapped logistic regression was used to generate a model to predict epileptogenicity of individual regions. RESULTS: Compared to nonepileptogenic structures, we found increased connectivity within epileptogenic regions ( P < .05) and between epileptogenic areas and other structures ( P < .01, paired t -tests, corrected). Epileptogenic areas also demonstrated higher clustering coefficient ( P < .01) and betweenness centrality ( P < .01), and greater decay of connectivity with distance ( P < .05, paired t -tests, corrected). Our connectivity model to predict epileptogenicity of individual regions demonstrated an area under the curve (AUC) of 0.78 and accuracy of 80.4%. CONCLUSION: Our study represents a preliminary step towards defining resting-state SEEG connectivity patterns to help localize epileptogenic brain regions ahead of neurosurgical treatment without requiring seizure recordings.